Interdependence of government expenditure among European countries: Productivity spillover and strategic interaction - Xiaodong Chen; Haoming Mi; Peng Zhou (Cardiff University, Cardiff Business School, 2025)
We build an endogenous growth model that distinguishes productive and welfare government expenditures and embeds fiscal externalities. The model yields three testable hypotheses: (i) productive expenditure raises growth (Barro effect); (ii) productive expenditure generates cross-country productivity spillovers; (iii) government expenditure structure exhibits spatial dependence. Estimation with a spatial-panel dataset for 30 European economies (EU27+3) corroborates all three hypotheses. We further show that positive productivity externalities induce an international free-rider problem, causing systematic under-investment in productive expenditure, while negative welfare externalities trigger a "welfare tournament" and over-spending on non-productive expenditure.
Keywords: E62; R58; 330; Fiscal Interdependence; Productivity Spillover; Strategic Interaction; SpatialPanel; Government Expenditure; Endogenous Growth